The concept of Archipelago Islam: A Critical Historical Study - Hayani, Aida; Ari Dwi Rahmawati; Ika Tri Susilowati; Akhmad Zulfikar Kabibulloh; Mohd. Farhan (SALIHA: Jurnal Pendidikan Islam, 2024)
Congress Nahdatul Ulama (NU) in Jombang, East Java which took place on August 1-5 2015. Since NU coined the term in 2015, the term “Islam Nusantara” has been widely misunderstood by several communities. " The questions that will be answered are First, Why was the term "Islam Nusantara" raised by NU circles at the 2015 MUNAS in Jombang? What is the history of the emergence and development of the term "Islam Nusantara" in Indonesia? What are the concept of "Islam Nusantara" can be able to adapt to Islamic teachings in the Indonesian context?. The purpose of this study is to understand more deeply the concept of Islam Nusantara, a critical historical study, this paper will use a historical approach to explore the historical roots of the emergence and development of the term "Islam". This research is used qualitative method and its approach to literature review. This analysis data in this research ara reduction data, display data, verification and conclusion. The results of the study stated that 1) the idea of Islam Nusantara is related to the political dimension, 2) Islam Nusantara brings a pluralist pattern to Islam and 3) the idea of Islam Nusantara is not representative so that it does not accommodate it as a whole.